2006
DOI: 10.1007/s11664-006-0254-2
|View full text |Cite
|
Sign up to set email alerts
|

Current status of large-area MOVPE growth of HgCdTe device heterostructures for infrared focal plane arrays

Abstract: This paper reviews the current status of the growth of fully doped HgCdTe (MCT) devices by metalorganic vapor phase epitaxy (MOVPE). The current reactor system has been developed to produce 3-inch diameter epitaxial layers compatible with slice-scale processing. The new reactor system has achieved routine epitaxial growth of MCT with good morphology onto both gallium arsenide (GaAs) and GaAs on silicon (Si) wafers that were oriented (2-8°) off (100) orientation. The density of surface defects (so-called ''hill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Mitra et al 27 found the As to be 15% to 50% active after a Hg vacancyfilling anneal, which increased to near 100% if a high-temperature anneal was included. More recently Maxey et al 28,29 have reported $100% activation after vacancy annealing alone. Additionally, minority carrier lifetimes comparable with Hg-rich LPE 27 were achieved.…”
Section: Literature Review Of Arsenic Doping In Mctmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitra et al 27 found the As to be 15% to 50% active after a Hg vacancyfilling anneal, which increased to near 100% if a high-temperature anneal was included. More recently Maxey et al 28,29 have reported $100% activation after vacancy annealing alone. Additionally, minority carrier lifetimes comparable with Hg-rich LPE 27 were achieved.…”
Section: Literature Review Of Arsenic Doping In Mctmentioning
confidence: 99%
“…(Me 2 N) 3 As is now the As doping precursor of choice. 28,30 It can be seen from the above that, if the As is inactive as grown, then low-temperature (200°C to 250°C) Hg-rich mercury vacancy anneals are insufficient to activate it. A Hg-rich high-temperature (400°C to 500°C) anneal followed by a vacancyfilling anneal are required and even that may not be sufficient.…”
Section: Literature Review Of Arsenic Doping In Mctmentioning
confidence: 99%
“…Several approaches to prevent hillocks creation have been tried: zinc nucleation layer, different Cd/Te ratios, different substrates orientations have been used, but we were not able to grow hillocks-free layer in controllable way on GaAs substrates. According to literature, only Selex Galileo reported on suppression of hillocks density below 5 cm -2 in the (100) HgCdTe grown on GaAs (Maxey et al 2000(Maxey et al , 2006. Therefore, most of our reported MWIR HgCdTe N ?…”
Section: Introductionmentioning
confidence: 74%
“…The growth process was optimized for photoelec− tronic devices operating at near−room temperature. Typi− cally, (111)B HgCdTe layers are grown on (100) GaAs with 3 deg off <110> orientation, which is enforced with suitable growth condition [7]. The (111) growth is characterized by important advantages, as it proceeds faster, provides hill− ock−free surface and ensures more efficient iodine doping with low precursor concentration [8].…”
Section: Methodsmentioning
confidence: 99%